Lingkungan Wana Wisata Grape Sebagai Sumber Media Belajar Tumbuhan Paku Bagi Siswa Sekolah Menengah - Ani Sulistyarsi (Jurnal Pendidikan, 2009)
This research is attempted to identify the types of pteri-dophyta in the ecosystem of tropical forest of Wana Grape, Wungu Subdistrict as one of Madiun’s tourism sites, so as to serve as the learning resources of biology subject. In this research, pteridophyta is classified base don its morphological structure – root, stem, leaves, branching system, fur, skin and ites reproduction system. The data are drawn from February 2004 up to July 2004 under observation and documentation methods. The data are taken from Wana Grape, Wungu Subdistrict, Madiun Regency by collecting pteridophyta at the observation area. The samplea are then classsified in form of matric or table. The analysis results in identification of pteridophyta which tetantively belongs to 26 types under 18 families, 6 ethnics, 2 classes and 1 division. Most of pteridophytas found belong to polypodiaceae, some belong to Selaginellaceae, Lycopodiaceae, Gleicheniaceae, Cytheaceae and Hymenophyleaceae is very rarely found. Cyclorsorus can be found in alost all of places in the forest with and without the exposure to the sun. The pteridophyta which belongs to Alsophyla glauca J. Sm and Gleichenia lenearis Clarke can only be found in the area which is difficult to reach, like canons and cliffs. These two types of pteridophyta are often used by the people to cook, so that they are risky to extinct.